2017
DOI: 10.1002/pc.24324
|View full text |Cite
|
Sign up to set email alerts
|

Uniform fiber orientation and transcrystallization formed in isotactic polypropylene/short glass fiber composites via a shear‐induced orientation extrusion

Abstract: The orientation of short glass fibers (SGFs) and the interfacial interaction between SGFs and isotactic polypropylene (iPP) matrix play main roles in the final properties of the iPP/SGFs composites. Here we show a self-design shear-induced orientation extrusion (SIOE) to efficiently fabricate the iPP/SGFs composites with evenly dispersion and orientation of SGFs in the whole iPP matrix. The shear stress and the orientation of SGFs are also benefit to induce transcrystals which enhance the interfacial interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Compared with PI‐0, the bursting strength of PI‐3 was increased by 27.2%. Furthermore, the surface interaction between fiber and matrix can significantly enhance the mechanical properties of polymer composites 24,25 . From the above analysis, it can be concluded that the mechanical properties of aramid/PI aerogel composites were greatly improved as compared to that of pure aramid felt.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Compared with PI‐0, the bursting strength of PI‐3 was increased by 27.2%. Furthermore, the surface interaction between fiber and matrix can significantly enhance the mechanical properties of polymer composites 24,25 . From the above analysis, it can be concluded that the mechanical properties of aramid/PI aerogel composites were greatly improved as compared to that of pure aramid felt.…”
Section: Resultsmentioning
confidence: 90%
“…Furthermore, the surface interaction between fiber and matrix can significantly enhance the mechanical properties of polymer composites. 24,25 From the above analysis, it can be concluded that the mechanical properties of aramid/PI aerogel composites were greatly improved as compared to that of pure aramid felt. The mechanism of mechanical strength enhancement is mainly due to that the PI aerogel coating on the aramid fabric surface can produce strong interaction between fibers and aerogel coating, and provide better binding effect to the Obviously, the thermal stability of the aramid felt combined with PI aerogels was improved, which means that these aerogels composites were well-suited to high-temperature applications.…”
Section: Resultsmentioning
confidence: 92%
“…Another approach was to prepare composite materials to improve toughness, and a lot of reports were published about the preparation of composite materials. [29][30][31][32] In general, COC materials were melt-blended with polymers such as ethylene, propylene, 𝛼-alkene, diene, polar monomers, and their copolymers or terpolymers. Structural similarities between COCs and linear polyolefins, their binary blends could be attractive for the enhancement of stiffness and toughness of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…Li designed shear-induced orientation extrusion . [25,26] Two arcuate flow channels are designed in each orientation extrusion, which can generate extending flow and convergent flow at the same time, making the melt flow in the runner a typical fish-tail flow. This method can effectively promote the evenly dispersion and orientation of fillers in the matrix.…”
Section: Introductionmentioning
confidence: 99%